Distinct functional muscarinic receptors in guinea-pig gallbladder, ileum and atria - AKICI, AHMET; KARAALP, ATİLA (ACADEMIC PRESS LTD, 1999)
Objective. The contractile responses of guinea-pig gallbladder smooth muscle cells have been suggested to be mediated by M-3 and M-4 muscarinic receptors by different research groups. Therefore, in the present study, several pharmacological properties of cholinergic functions in guinea-pig gallbladder, guinea-pig ileum (mediated via M-3 receptors), and guinea-pig and rat atria (mediated via Mt receptors) were compared, Methods: The isometric contractions of isolated guinea-pig ileum, guinea-pig gallbladder, guinea-pig and rat atrial strips in in vitro organ bath were recorded on a polygraph and the effects of carbachol, oxotremorine, McN-A-343, and clozapine have been investigated. Results: Three muscarinic receptor agonists, carbachol, oxotremorine and McN-A-343 showed different order of potencies in their negative inotropic effects and contractile actions in guinea-pig gallbladder suggesting that functional muscarinic receptors in the gallbladder are distinct from those in the atria, and similar to M-4-subtypes. Clozapine which was shown to have antagonistic affinity for muscarinic M-1, M-2, M-3 and M-5, but partial agonistic affinity for muscarinic M-4 receptors, contracted gallbladder concentration-dependently. On the other hand, clozapine antagonised carbachol-induced ileal and gallbladder contractions and negative inotropic effects indicating that it acts like a partial agonist in the gallbladder. Conclusion: It was concluded that the contractile muscarinic receptors of guinea-pig gallbladder are distinct from those of atria (M-2) and ileum (M-3), but seem to be of M-4 subtype. (C) 1999 Academic Press.
Keywords: muscarinic; guinea-pig; gallbladder; ileum; atria; McN-A 343; oxotremorine; carbachol; clozapine; SMOOTH-MUSCLE; M-4 RECEPTORS; CHO-K1 CELLS; SUBTYPES; BINDING; HETEROGENEITY; ANTAGONIST; CLOZAPINE; CONTRACTION; CYCLASE